The Establishment and Activity of Military Achievers Union (1937-1940) - Aušra Jurevičiūtė (Lietuvos Istorijos Studijos)
Military Achievers Union was an organization of former soldiers. The establishment of the union was quite late as at the beginning of the First World War in 1914, large numbers of Lithuanians as Russian officials were already serving in the Russian army. When Germany occupied Lithuania in 1915, due to the early mobilization and call-up, about 30,000 Lithuanian soldiers were serving in all Russian fronts from Riga Bay to Caucasus.